Evaluation of oral changes in patients submitted to gastroplasty (Research, Society and Development, 2020)
Objective: to analyze the oral changes perceived by patients undergoing gastroplasty. Methodology: this is a cross-sectional, descriptive, quantitative study, carried out in the form of an online questionnaire, with 25 open and objective questions, with patients who underwent bariatric surgery for at least 1 year, in Maceió, Alagoas. The data were tabulated and evaluated by means of descriptive analysis based on the distribution of the absolute (n) and relative (%) frequency of the answers related to each evaluated question. Results: A total of 50 bariatric patients answered the questionnaire. Dental care was judged by 76% of those surveyed to be important in the pre- and postoperative period, however, 20% as perhaps and 4% not being necessary, however 84% did not receive any guidance on the subject and 42% are being followed up dental care. Among patients, 90% have exacerbated oral changes after surgery, such as: dry mouth, dry mouth, caries, tenderness, dental stones, bad breath and gastroesophageal reflux that cause deterioration of tooth enamel. Conclusion: there is a clear need for the dental surgeon to be included in the multiprofessional team for the prevention and progression of oral changes, reported by patients and described in the literature, as well as the accessibility of these patients in dental offices.